Competency of Teachers in the Utilization of Information and Communication Technology on Christian Education Learning - Tulung, Jeane Marie; Wuwung, Olivia Cherly; Wuwung, Olivia Cherly (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to determine how the competency of the teachers in the utilization of information technology and communication on the study of Christian Education in Manado city. The methodused in this study is survey research with a quantitative approach of descriptive.The result of this research was the competence of teachers in Manado city in the use of information technology and communication on the learning of Christian Education is medium, this is demonstrated by information created from the processing of competency data teachers in the mastery of software applications in learning is to control an average of 33.91% and slightly control the average of 42.62%, while for the average digital competency is 41.67% teacher mastery and 44.55% less mastered, the aspect of knowledge pedagogical average is 60.34 teacher mastered pedagogicalknowledge, and averaged 57.34% teachers mastered pedagogical knowledge and technology.